A measurement instrument to assess engineering students´ knowledge about sustainable development (LACCEI, 2024)
The purpose of this paper is to present a measurement instrument to evaluate the knowledge that engineering students have about sustainable development (SD) aspects. Sustainable development is a topic of upmost importance at the present, given the situation that our society is facing regarding the deterioration of our planet. This is mainly due to bad practices related to the way human beings have been using the resources the earth offers. The comprehension of the connection between our actions and the evolution of our planet are clearer now than before. The harmful effects of heat waves, draught, heavy rains, are among the phenomenon that tell us the earth is changing. In this sense, this study adopts a measurement instrument previously designed, to measure the understanding about SD among engineering students of Universidad Tecnológica de Panamá. The questionnaire was reviewed to adapt it to the reality of engineering students in Panama. The objective of the study is to present a measurement instrument capable of evaluating the understanding the students have about SD. A careful review of the literature was conducted to provide a good basis to confirm the main aspects that need to be incorporated into the question items. Four main aspects are proposed: environmental, economy, societal and educational aspects. Environmental aspects and SD are directly related, any development that humankind sets to accomplish has an impact on the environment and therefore on the sustainability of the world. Economy aspects are also strongly related to SD, the elimination of income inequalities, the empowerment of women, the promotion of youth employment and decent work for everyone are key objectives of SD. The full participation of the citizens in the economic system of every nation is a requirement of the agenda of SD. The societal dimension considers that every person has the responsibility as part of the society, to take action and protect the planet we live in. The new generations should be more aware of the role they could play as members of their community, solving problems and communicating effectively to make positive transformations. Finally, the educational aspects Students should acquire the competences that empower them to be proactive towards finding solutions for the environmental problems. The main purpose of education for SD should be to empower the students to be active in society and make changes that contribute to SD. In this regard, the teaching methodology should always set clear goals to accomplish students´ understanding of sustainable issues.